Protracted vegetation recovery after compound drought and hot extreme compared to general drought - Mengtian Huang; Panmao Zhai (Environmental Research Letters)
Recovery time is critical for accurate assessment of drought impacts on vegetation growth and terrestrial carbon dynamics. However, the dominant factors driving the spatiotemporal variation of recovery time are still poorly understood; hardly any research has focused on the comparison of recovery time between general drought and compound dry-hot events. This study examined recovery time of vegetation greenness post different drought types during 1982–2016 and attempted to identify the predominant factors determining vegetation recovery time over the globe. Our findings demonstrated protracted recovery of vegetation greenness after compound drought and hot extreme (CDHE) event compared to general drought in 68% of global vegetated area. Deciduous broadleaved forest exhibited the most remarkable difference between recovery time post CDHE (13.8 ± 5.6 months) and post general drought (9.3 ± 4.7 months). We also revealed that post-event moisture condition and long-term precipitation were the chief impact factors of drought recovery time.